(3HZjI GdYdeGA hGdQhGI aj GdPjd YdicJGH TjNi aj GdbVGIs - (3TeS GdOjf CHi GdNjQ eMeO Hf eMeO Hf YHO GdQMef Hf eMeO GdSNGhis; (3TgGH GdOjf CHh GdaVd CMeO Hf Ydj Hf MLQ GdYSbdGfi,J (B852 (3g` s ((3Ydi Hf CMeO Hf YeQ GdebQi Gdjefi GdTgjQ HGdThGjWi s)
(3ChdgG (B:s
(3hcP MaX GdeYfi ddLHGQi hGdeNJGQ hGdefXheI s
(3BNQgG (B:s
(3hde jdHK Gf GSJbQ hdOg GdHOQi eMeO ai hXjaI hcJHJ HecI hBNQ GdaQGZ ef cJGHJg s
(3GfXQ Qbe (B91 " (3JGQjNs
(3fSNI KGfjIs
(3hYdjgG NW GdeDda ai YOI ehGVYs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs